(untitled) (Global Journal of Science Frontier Research, 2011)
This study aimed at looking into ways of improving the nutritive values of sorghum Stover grown under two conditions: one grown sole and another intercropped with groundnuts. As an abundant source of dry season feeds, the study was conducted to determine its nutritional value and digestibility. Nine Yankasa rams weighing 22±2.5 kg, age between 6 and 12 months were used in this experiment. Rams were completely randomized into three treatments with three rams per treatment. Treatment one was sole sorghum, treatment two intercropped sorghum Stover plus 200 grams groundnuts hulms. Treatment three intercropped Stover plus 400 grams of groundnut hulms. Result of the analysis showed that there was an increase in the rate of digestibility in intercropped Stover fed with supplement. This could be due to high nitrogen content available to ruminal bacteria in the intercropped Stover and supplements, which was not in the sole grown Stover. Based on this result, the experiment recommends the intercropping of sorghum with groundnuts to improve law nutrients value and digestibility. At 200 and 400 grams levels of supplementation there was significant increase at (P